2009
DOI: 10.1021/bi802036b
|View full text |Cite
|
Sign up to set email alerts
|

α-Hederin, but Not Hederacoside C and Hederagenin fromHedera helix, Affects the Binding Behavior, Dynamics, and Regulation of β2-Adrenergic Receptors

Abstract: Hederacoside C, alpha-hederin, and hederagenin are saponins of dry extracts obtained from the leaves of ivy (Hedera helix L.). Internalization of beta(2)-adrenergic receptor-GFP fusion proteins after stimulation with 1 microM terbutaline was inhibited by preincubation of stably transfected HEK293 cells with 1 microM alpha-hederin for 24 h, whereas neither hederacoside C nor hederagenin (1 microM each) influenced this receptor regulation. After incubation of A549 cells with 5 nM Alexa532-NA, two different diffu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
75
0
9

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(89 citation statements)
references
References 10 publications
1
75
0
9
Order By: Relevance
“…20) Additionally, glycyrrhizin injection attenuates the development of carrageenan-induced lung injury in CD mice. 21) Recently, Sieben et al 22) found that pre-incubation for 24 h with the saponin compound R-hed-erin could inhibit the terbutaline-stimulated internalization of the b 2 AR, which is in agreement with the fact that saponins are cholesterol-complexing agents and that cholesterol depletion is known to inhibit receptor internalization. [23][24][25][26] Chemically, glycyrrhizin is a triterpenoid saponin glycoside, therefore, we hypothesized that glycyrrhizin may have a positive effect on the regulation of b 2 AR agonist-induced internalization of b 2 ARs.…”
mentioning
confidence: 67%
“…20) Additionally, glycyrrhizin injection attenuates the development of carrageenan-induced lung injury in CD mice. 21) Recently, Sieben et al 22) found that pre-incubation for 24 h with the saponin compound R-hed-erin could inhibit the terbutaline-stimulated internalization of the b 2 AR, which is in agreement with the fact that saponins are cholesterol-complexing agents and that cholesterol depletion is known to inhibit receptor internalization. [23][24][25][26] Chemically, glycyrrhizin is a triterpenoid saponin glycoside, therefore, we hypothesized that glycyrrhizin may have a positive effect on the regulation of b 2 AR agonist-induced internalization of b 2 ARs.…”
mentioning
confidence: 67%
“…Typical reported activities include anti-inflammatory [78,79], antiviral [80], antifungal [81], antibacterial, mucolytic, antispasmodic agent and in vitro bronchodilatory [82,83].…”
Section: Phytochemicals -Isolation Characterisation and Role In Humamentioning
confidence: 99%
“…The most frequently www.intechopen.com mentioned indications were urogenital tract disorders, respiratory system disorders, gastrointestinal tract disorders, skin ailments, blood system disorders, nervoussystem disorders, cardiovascular system disorders, and rheumatism (ˇSari´c-Kundali´c et al, 2010). Ivy leaf contains spooning which are considered to have mucolytic, spasmolytic, bronchodilatory and antibacterial effects (Sieben et al, 2009;Gepdiremen et al, 2005). Despite widespread use of ivy leaf extracts, the effectiveness for the treatment of acute cough is not well established (Holzinger & Chenot, 2011).…”
Section: Use Reasons Of Herbal Medicinementioning
confidence: 99%
“…More and more physicians are either referring patients to herbal practitioners or practising phytotherapy themselves (Gepdiremen et al, 2005). US sales figures for herbal remedies have risen almost exponentially and, in 1997, exceeded $US350 million (Sieben et al, 2009). HMPs are used to treat a large variety of conditions as well as for 'maintenance of health', i.e.…”
Section: Cost Of Herbal Medicinementioning
confidence: 99%